The Application Of The Make A Match Type Of Cooperative Learning Model To Improve Social Studies Learning Outcomes 5TH Grade UPT SPF SDN KIP Bara-Baraya I Makassar City - Sayidiman Sayidiman; Bhakti Prima Findiga Hermuttaqien; Nur Aulia Aisya (International Journal of Elementary School Teacher, 2023)
The problem that lies behind this research is the low learning outcomes of students in social studies subject class V UPT SPF SDN KIP Bara-Baraya I Makassar City. This study aims to describe the application of the make a match type of cooperative learning model to improve social studies learning outcomes in class V UPT SPF SDN KIP Bara-Baraya I Makassar City. The focus of this researchis the application of the make a match type of cooperative learning model and student learning outcomes. The reasearch approach used in this study is a qualitative approach and the type of research used is Classroom Action Reasearch (CAR) which was carried out in two cycle, each cycle consists of two meetings. Each cycle has four stages, namely the planning stage, the implementation stage, the observation stage, and the reflection stage. Data collection techniques and procedures are observation, tests and documentation. This Classroom Action Reasearch (CAR) wa carried out in class V UPT SPF SDN KIP Bara-Baraya I Makassar City with the research subjects being teachers and students totaling 18 people consisting of 13 male atudents and 5 female students. The data analysis technique in this research is qualitative and quantitative (mixed method) data analysis. The results showed that there was an increase in student learning outcomes in social studies subjects with the achievement of completeness of pre action learning outcomes in the less category, in the first cycle obtained 8 students complete with the achievement of mastery learning outcomes was in the sufficient category, while in the second cycle 15 students were obtained trough the achievement of complete learning in the good category. The conclusion in this study is that the application of the make a match type of cooperative learning model can improve student learning outcomes in social studies subjects for class V UPT SPF SDN KIP Bara-Baraya I Makassar City.